İlkokul 4. sınıf öğrencilerinin okuma motivasyonu ve okur öz algılarının çeşitli değişkenler açısından incelenmesi - Okur, Burçin (My University, 2017)
Bu araştırmada, ilkokul 4. sınıf öğrencilerinin okuma motivasyonu ve okur öz algılarının çeşitli değişkenler açısından incelenmesi ve aralarındaki ilişkinin belirlenmesi amaçlanmıştır. İlişkisel tarama modeli çerçevesinde yürütülen bu araştırmada aşağıdaki sorulara cevap aranmıştır: 1.İlkokul 4. sınıf öğrencilerinin okuma motivasyonu düzeyleri nedir? 1.1.Öğrencilerin okuma motivasyonu düzeyleri cinsiyete göre farklılaşmakta mıdır? 1.2.Öğrencilerin okuma motivasyonu düzeyleri anne eğitim durumuna göre farklılaşmakta mıdır? 1.3.Öğrencilerin okuma motivasyonu düzeyleri baba eğitim durumuna göre farklılaşmakta mıdır? 1.4.Öğrencilerin okuma motivasyonu düzeyleri okul öncesi eğitim alma durumuna göre farklılaşmakta mıdır? 2.İlkokul 4. sınıf öğrencilerinin okur

algı düzeyleri nedir? 2.1.Öğrencilerin okur öz algı düzeyleri cinsiyete göre farklılaşmakta mıdır? 2.2.Öğrencilerin okur öz algı düzeyleri anne eğitim durumuna göre farklılaşmakta mıdır? 2.3.Öğrencilerin okur öz algı düzeyleri baba eğitim durumuna göre farklılaşmakta mıdır? 1.1.Öğrencilerin okur öz algı düzeyleri okul öncesi eğitim alma durumuna göre farklılaşmakta mıdır? 2.İlkokul 4. sınıf öğrencilerinin okuma motivasyonları ile okur öz algıları arasında ilişki var mıdır? Araştırmanın örneklemini uygun örnekleme yöntemiyle seçilen, 2014-2015 eğitim-öğretim yılında İstanbul’un Tuzla, Pendik, Çekmeköy ve Kadıköy ilçelerinde yer alan sekiz devlet okulunda öğrenim görmekte olan 556 adet 4. sınıf öğrencisi oluşturmaktadır. Araştırmada veri toplama aracı olarak, bir kişisel bilgi formu ve iki ölçme aracı kullanılmıştır. Kişisel bilgiler formu, öğrencilerin cinsiyeti, anne-babanın eğitim durumu ve öğrencinin okul öncesi eğitim alıp almadığı hakkında bilgi edinmek amacıyla araştırmacı tarafından hazırlanmıştır. Araştırmada kullanılan ölçeklerden biri Guthrie ve Wigfield (1997) tarafından geliştirilmiş ve Yıldız (2010) tarafından 3, 4 ve 5. sınıf öğrencileri için Türkçe’ye uyarlama, geçerlik ve güvenirlik çalışması yapılmış olan Okuma Motivasyonu Ölçeği’dir. Diğeri iseHenk ve Melnick (1995) tarafından geliştirilen ve Yaylı ve Duru (2008) tarafından 4 ve 5. Sınıf öğrencileri için Türkçe’ye uyarlama, geçerlik ve güvenirlik çalışması yapılmış olan Okur Öz Algılama Ölçeği’dir. Okuma Motivasyonu Ölçeği ve Okur Öz Algılama Ölçeği’nin bu çalışma için uygunluğu birer madde analizi ile yeniden güvenirlik katsayılarına bakılarak incelenmiştir. Yapılan madde analizlerine göre ölçeklerin (okuma motivasyonu ölçeği α=0,872, okur öz algılama ölçeği α=0,934) ve alt boyutlarının güvenirlik düzeylerinin araştırma için yeterli olduğu anlaşılmıştır.Öğrencilerin, Kişisel Bilgiler Formu, Okuma Motivasyonu Ölçeği veOkur Öz Algılama Ölçeği ile toplanan verilerin tümü, SPSS (Statistical Package for the Social Sciences) 23 istatistik mlemeye tabi tutulmuştur. Analiz için frekans ve yüzde dağılımları, ortalama ve standart sapma değerleri, Kolmogorov-Smirnovtesti, ilişkisiz gruplar t-testi, Kruskal-Wallistesti, Mann-Whitney U testi ve Pearson korelasyon katsayıları kullanılmıştır. İlkokul dördüncü sınıf öğrencilerinin genel okuma motivasyonu yüksek düzeydedir. Öğrencilerin okumaya yönelik dışsal motivasyon düzeyleri, içsel motivasyon düzeylerinden daha yüksektir. İçsel motivasyonda ‘merak’ boyutu, dışsal motivasyonda ise ‘uyum’ boyutu düzeyi diğer boyutlara göre daha yüksektir. Öğrencilerin okumaya yönelik içsel motivasyon düzeyleri cinsiyete göre farklılaşmaktadır. Kız öğrencilerin içsel motivasyonu erkek öğrencilerin içsel motivasyonuna göre daha yüksektir. İçsel motivasyonun alt boyutu olan ‘ilgi’ boyutunda cinsiyet açısından bir farklılaşma bulunamamıştır. ‘Merak’ boyutunda ise anlamlı bir fark bulunmuştur ve bu fark kız öğrencilerin lehinedir. Öğrencilerin okumaya yönelik dışsal motivasyon düzeyleri arasında da bir farklılaşma söz konusudur. Kız öğrencilerin dışsal motivasyonu erkek öğrencilere göre daha yüksektir. Dışsal motivasyonun alt boyutları olan tanınma, sosyal, rekabet ve uyum boyutları düzeylerinin hepsinde cinsiyet açısından anlamlı bir fark vardır ve bu fark her boyut için kız öğrencilerin lehinedir. Öğrencilerin okumaya yönelik içsel motivasyon ve içsel motivasyon alt boyutları (ilgi, merak) düzeyleri ile okumaya yönelik dışsal motivasyon ve dışsal motivasyon alt boyutları (tanınma, sosyal, rekabet, uyum) düzeyleri anne ve baba eğitim durumlarına göre farklılaşmaktadır. Anne eğitim düzeyi arttıkça içsel ve dışsal motivasyon ile alt boyutları düzeylerinde bir artış görülmektedir. Baba eğitim düzeyi arttıkça da aynı durum söz konusudur. Okul öncesi eğitim alma durumuna göre de hem okumaya yönelik içsel motivasyon ve içsel motivasyon alt boyutları (ilgi, merak) düzeyleri hem de okumaya yönelik dışsal motivasyon ve dışsal motivasyon alt boyutları (tanınma, sosyal, rekabet, uyum) düzeyleri farklılaşmaktadır. Okul öncesi eğitim alan öğrencilerin okumaya yönelik içsel ve dışsal motivasyon düzeyleri alt boyutlarında da geçerli olmak üzere okul öncesi almayan öğrencilere göre daha yüksektir. Genel olarak, öğrencilerin okur öz algı düzeyleri yüksektir. Öğrencilerin öz algıları en yüksek düzeyde ‘gelişim’ boyutundadır. Gelişim boyutunu sırasıyla ‘fizyolojik durumlar’, ‘aileden alınan sosyal dönüt’, ‘arkadaş ve öğretmenden alınan sosyal dönüt’ ve ‘gözleme dayalı karşılaştırma’ boyutları takip etmektedir. Öğrencilerin genel okur öz algı düzeyleri arasında cinsiyete göre anlamlı bir fark vardır. Kız öğrencilerin öz algı düzeyleri erkek öğrencilere göre daha yüksektir. Kız ve erkek öğrencilerin öz algı ‘gelişim’ ve ‘gözleme dayalı karşılaştırma’ boyutlarında düzeyleri arasında anlamlı bir farklılaşma bulunmazken; kız öğrencilerin öz algı ‘fizyolojik durumlar’, ‘arkadaş ve öğretmenden alınan sosyal dönüt’ ve ‘aileden alınan sosyal dönüt’ boyutları düzeyleri erkek öğrencilere göre daha yüksektir. Öğrencilerin öz algı ve öz algı alt boyutları (gelişim, fizyolojik durumlar, arkadaş ve öğretmenden alınan sosyal dönüt, gözleme dayalı karşılaştırma, aileden alınan sosyal dönüt) düzeyleri anne ve baba eğitim durumlarına göre farklılaşmaktadır. Anne eğitim düzeyi arttıkça öz algı ve alt boyutları düzeylerinde bir artış görülmektedir. Baba eğitim düzeyi arttıkça da aynı durum söz konusudur. Okul öncesi eğitim alma durumuna göre de öz algı ve alt boyutları düzeyleri farklılaşmaktadır. Okul öncesi eğitim alan öğrencilerin okur öz algı düzeyleri alt boyutlarında da geçerli olmak üzere okul öncesi almayan öğrencilere göre daha yüksektir. Araştırmanın son bulgusuna göre öğrencilerin, okur öz algı düzeyleri ile içsel motivasyon düzeyleri arasında da öz algı düzeyleri ile dışsal motivasyon düzeyleri arasında da pozitif yönde ve anlamlı bir ilişki söz konusudur. ABSTRACT The aim of this study was to analyse reading motivation and reader self perceptions of the 4th grade primary school students in terms of various variables and determine the relation between reading motivation and self perceptions of them. The study was carried out in the relational screening model and ought to answer following questions: 1.What is the level of 4th graders’ reading motivation? 1.1.Does the students’ level of reading motivation differ depending on gender? 1.2.Does the students’ level of reading motivation differ depending on mother’s educational background? 1.3.Does the students’ level of reading motivation differ depending on father’s educational background? 1.4.Does the students’ level of reading motivation differ depending on their pre-school educational background? 2.What is the level of 4th graders’ reader self perceptions? 2.1.Does the students’ level of reader self perceptions differ depending on gender? 2.2.Does the students’ level of reader self perceptions differ depending on mother’s educational background? 2.3.Does the students’ level of reader self perceptions differ depending on father’s educational background? 1.1.Does the students’ level of reader self perceptions differ depending on their pre-school educational background? 2.Is there a relation between reading motivation and reader self perceptions of the 4th graders? The sample of this research which was selected by convenience sampling consists of 556 fourth grade students who received education in 8 public schools in 2014-2015 academic year in Tuzla, Pendik, Çekmeköy and Kadıköy districts in İstanbul. A ‘personal information form’ and two evaluation instruments were implemented as data collection tools in this study. The personal information form was prepared by researcher in order to obtain information about the gender of the students, the educational background of parents and whether the students receive preschool education or not. One of the evalution instruments is Motivation for Reading Questionnaire which was developed by Guthrie&Wigfield (1997) andit is adapted to Turkish, its validity and reliability study was done by Yıldız (2010) for 3, 4 and 5th graders. The other evaluation instrument is Reading Self-Perception Scale which was developed by Henk&Melnick (1995) and it is adapted to Turkish, its validity and reliability study was done by Yaylı&Duru (2008) for 4th and 5th graders. Convenience of Motivation for Reading Questionnaire and Self-Perception Scalefor this study was analysed by viewing realibity factors again with item analysis. It is found that the level of scales (motivation for reading questionnaire α=0,872, reading self-perception scale α=0,934) and their sub-dimensions’ realibility is convenient for the research according to item analysis.The data collected by personal information form, Motivation for Reading Questionnaire and Self-Perception Scale were analysed with SPSS (Statistical Package for the Social Sciences) 23 statistical programme. For the analysis frequency and percentage distribution, mean square and standart deviation values, Kolmogorov-Smirnov test, unrelated samples t-test, Kruskal-Wallis test, Mann-Whitney U test and Pearson coefficient of correlation were used. The general reading motivation of 4th graders is at high level. Students’ level of extrinsic reading motivation is higher than their level of intrinsic reading motivation. In intrinsic motivation the level of curiosity dimension is higher than others; in extrinsic motivation the level of compliance dimension is higher than others. The level of students’ intrinsic motivation varies by gender. The level of girls’ intrinsic motivation is higher than the level of boys’ intrinsic motivation. The interest dimension which is a sub-dimension of intrinsic motivation doesn’t vary by gender. The curiosity dimension which is another sub-dimension of intrinsic motivation varies by gender and girls’ level of curiosity dimension is higher than boys’. The level of students’ extrinsic motivation varies by gender too. The level of girls’ extrinsic motivation is higher than the level of boys’ extrinsic motivation. All of the sub-dimensions of extrinsic motivation; recognize, social, competition and compliance vary by gender and for all dimensions girls’ levels are higher than boys’ levels. The instrinsic reading motivation of students with its sub-dimensions (interest, curiosity) and the extrinsic reading motivation of students with its sub-dimensions (recognize, social, competition, compliance) vary by mother’s and father’s educational background. The more educational level of mother gets higher the more level of intrinsic and extrinsic motivations with their sub-dimensions increases. The more educational level of father gets higher just like it does. The instrinsic reading motivation of students with its sub-dimensions (interest, curiosity) and the extrinsic reading motivation of students with its sub-dimensions (recognize, social, competition, compliance) vary by pre-school educational background. The students who have pre-school educational background have higher level of intrinsic and extrinsic motivation with their sub-dimensions than the students who doesn’t have pre-school educational background. The general reading self perception of 4th graders is at high level. The highest self perception level is at ‘progress’ dimension. ‘Physiological states’, ‘social feedback from family’, ‘social feedback from friends and teacher’ and ‘observational comparison’ dimensions follow level of ‘progress’ dimension in a row. The generel self perception levels of students vary by gender. The reading self perception level of girls higher than the reading self perception of boys. When the levels of ‘progress’ and ‘observational comparison’dimensions of students don’t vary by gender, girls’ levels of ‘physiological states’, ‘social feedback from friends and teacher’ and ‘social feedback from family’ dimensions are higher than boys’ levels. The level of students’ self perception with its sub-dimensions (progress, physiological states, social feedback from friends and teacher, observational comparison, social feedback from family) vary by mother’s and father’s educational background. The more educational level of mother gets higher the more level of reader self perception with their sub-dimensions increases. The more educational level of father gets higher just like it does. The reader self perception of students with its sub-dimensions vary by pre-school educational background. The students who have pre-school educational background have higher level of reader self perception with its sub-dimensions than the students who doesn’t have pre-school educational background. According to last finding of the research, there is a high and significant correlation both between reader self perception and intrinsic reading motivation level and between reader self perception and extrinsic reading motivation level of the students.
Keywords: Eğitim ve öğretim (İlk); Okuma motivasyonu; Türkiye